ANALISIS PERENCANAAN TINGKAT PUSKESMAS DI KOTA MEDAN TAHUN 2012 - shiska Dhewi; Heldy BZ; Fauzi siregar (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACT The implementation of the planning to health centers in Medan is guided by the Standard Manual for Health Center. The main purpose of planning to helth center is to prevent any problems on public health, it shall be due to public health, the effort to health development or for supporting to public health. In addition, it aims to improve performance of health center in arranging the annual activities with plans for health center capable to do activities efficiently, effectively and shall be accountable. This research was a survey with qualitative approach witch was aimed to explain how the planning of the health centers in Medan for 2012. The primary data were collected by thorough interviews, and the secondary data were obtained from the health service Medan. The informants to this research comprised of 10 persons, one head of program and planning of the city health service in Medan, three head of health centers (Health centers of Glugur Darat, Kampung Baru, and Kedai Durian), and ten staff for health centers. The result of the research showed that all the informants had known the planning of the health centers in Medan city. The health centers in Medan was do or arrange it well with term POA (Plan Of Action) that has been done routinely annually. For 2012, there is not done yet any special training about the planning, it is shortage of fund reasonable, the health centers mostly aware the points of planning to execute and fortunately in generally according to four phases, such as pre-planning, analysis on situation, arrange the plan of activity and arrange the plan of implementation. For all the phases has been done properly. It is encouraged to all Health Centers available on Medan city more passionateto havea better official planning and do it optimally based on the problems dealth with as usual and also to improve the human resources available. Keywords : the planning of the health centers.